Bisnis Waralaba Dalam Perspektif Hukum Kontrak - Lina Maulidiana (PRANATA HUKUM, 2014)
Franchise is one of business model between two or more companies/individuals in which one party serves as franchisor and the other one as franchisee which enable the franchisee to benefit the franchise business and or to use the intellectual property rights. It is also defined as an agreement of one party as its characteristic under a license and the franchisor owns the royalty rights. The ideal basic concept of franchise business within the perspective of contract law follows the values of fairness and equity in accordance with contract lawâs principles as described in a seminar about âThe Book of The Law of Civil Law Reformsâ hold by National Law Development Board in 1981 stated that the new contract constitutions will be established under some principles like: freedom of holding the contract, protection of low economic classes, proper intention, conformity, decency, public interest, legal certainty, pacta sunt servanda, and proportionality. The construction of contract law adopts the nine principles above .It is hoped that the interest of both franchisor and franchisee is fulfilled and well balanced.